The Role of Stakeholder Collaboration in Improving Supply Chain System Performance and Sustainability - Ade Suhara; Suprayitno; Imam Jayanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Global supply chains face challenges like demand fluctuations, supply uncertainties, and changing regulations, making stakeholder collaboration vital for performance and sustainability. This study examines how collaboration among suppliers, manufacturers, distributors, customers, NGOs, and regulators enhances supply chain efficiency and resilience. Through a qualitative review of literature from 2020–2025, sourced from Scopus, Web of Science, and Google Scholar, the analysis highlights that collaboration reduces lead times, optimizes logistics, lowers costs, and integrates environmental and social objectives. Key success factors include trust, clear communication, aligned objectives, technology adoption, long-term commitment, and skilled human resources. However, barriers such as conflicting interests, technological disparities, trust deficits, global complexities, and high initial costs pose challenges. Case studies like Unilever’s “Partner to Win” and Walmart’s Project Gigaton show significant reductions in CO₂ emissions, cost savings, and environmental impact through effective stakeholder coordination. The findings emphasize that integrated digital platforms, strong governance, and multicultural management skills are critical for advancing sustainable collaboration in global supply chains.